2015
DOI: 10.1016/j.ijmyco.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm infection among patients with pulmonary tuberculosis: Impact of co-infection on the therapeutic failure of pulmonary tuberculosis

Abstract: In conclusion, the rate of therapeutic failure of pulmonary TB is high. Besides older age and DM, hookworm infection can reduce the therapeutic response of pulmonary TB. Screening for and control of DM and hookworm infection among patients with pulmonary TB may improve their therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
10
2
1
Order By: Relevance
“…Our finding was high compared to a report in Egypt (16%) 9 and China (21.7%). 48 The Egyptian study 9 was only assessed the burden of a single parasite, which was not a dominant parasite in our finding. In our study, Ascaris lumbricoides was the dominant parasite.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our finding was high compared to a report in Egypt (16%) 9 and China (21.7%). 48 The Egyptian study 9 was only assessed the burden of a single parasite, which was not a dominant parasite in our finding. In our study, Ascaris lumbricoides was the dominant parasite.…”
Section: Discussioncontrasting
confidence: 82%
“…7 In Africa, one-third of TB patients have an IPI 8 that contributes to the high rate of therapeutic failure of pulmonary TB. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Among the 12 types of intestinal parasites identified, A.lumbricoides and H.worm were found to be the most frequently reported intestinal parasites. Likewise, studies from Tanzania [6] and Egypt [36] reported supportive findings. Among intestinal protozoans, G.lamblia was reported frequently compared with other intestinal protozoans.…”
Section: Discussionmentioning
confidence: 70%
“…As shown in Fig 1, we found a total of 1594 papers following the initial search of databases, and after excluding duplicates and/or non-eligible papers, 20 articles had eligibility to be considered in the current systematic review and meta-analysis [9,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The Kappa test between the reviewers showed interobserver agreement of 93.75%, which was considered to be an excellent result.…”
Section: Study Characteristicsmentioning
confidence: 99%